2020
DOI: 10.1096/fj.201900139r
|View full text |Cite
|
Sign up to set email alerts
|

Heterochromatin protein 1γ deficiency decreases histone H3K27 methylation in mouse neurosphere neuronal genes

Abstract: Heterochromatin protein (HP) 1γ, a component of heterochromatin in eukaryotes, is involved in H3K9 methylation. Although HP1γ is expressed strongly in neural tissues and neural stem cells, its functions are unclear. To elucidate the roles of HP1γ, we analyzed HP1γ ‐deficient (HP1γ KO) mouse embryonic neurospheres and determined that HP1γ KO neurospheres tended to differentiate after quaternary culture. Several genes normally expressed in neuronal cells were upregulated in HP1γ KO undifferentiated neurospheres,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
(108 reference statements)
0
2
0
Order By: Relevance
“…Since heterochromatin that is characterized by H3K9me2 and binding of HP1γ is also associated with a histone de‐acetylation on H3K27 (Naruse et al, 2020; Wang et al, 2019), we sought to investigate whether inhibiting the de‐acetylation of histones in oocytes will cause a similar effect. Previous reports also showed that treatment with a histone deacetylase (HDAC) inhibitor affects oocyte maturation in vitro (Jin et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Since heterochromatin that is characterized by H3K9me2 and binding of HP1γ is also associated with a histone de‐acetylation on H3K27 (Naruse et al, 2020; Wang et al, 2019), we sought to investigate whether inhibiting the de‐acetylation of histones in oocytes will cause a similar effect. Previous reports also showed that treatment with a histone deacetylase (HDAC) inhibitor affects oocyte maturation in vitro (Jin et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…5C, S9). Since heterochromatin that is characterized by H3K9me2 and binding of HP1γ is also associated with a histone de-acetylation on H3K27 (Naruse et al, 2020) (Wang et al, 2019), we sought to investigate whether inhibiting the deacetylation of histones in oocytes will cause a similar effect. Previous reports also showed that treatment with a histone deacetylase (HDAC) inhibitor affects oocyte maturation in-vitro (Jin et al, 2014).…”
Section: Resultsmentioning
confidence: 99%